Prosedur Pelaporan SPT Tahunan Wajib Pajak Orang Pribadi Melalui e-Filing pada KJA ABC - Novika Putri Pratiwi; Tituk Diah Widajantie (Institut Nalanda, 2023)
The field of taxation is one sectors that contributes significantly to state revenues. So that tax revenue is expected to continue to be increased. The push for an increase in taxes is the reason for administrative modernization. One form of tax modernization is the application of e-Filing in tax submission. The purpose of this study is to find out how the procedure for reporting the annual SPT of individual taxpayers is done through e-Filing at the KJA ABC. The method used is descriptive research with a qualitative approach. Information procedure for obtaining use observation and interview techniques. On the basis of the results and discussion of this study, the KJA ABC has reported the annual SPT of individual taxpayers by the Regulation of the Directorate General of Taxes Number PER-01/PJ/2014. However, there are still obstacles for taxpayers who do not provide complete and correct information, which hinders the annual SPT reporting procedure by the tax consultant. So it is hoped that tax consultants can be more assertive and make deeper observations of taxpayers who use tax services.